Aerothermal characteristics of lateral channel flows with novel latticework morphologies - Shyy Woei Chang; Yong-En Lu (Case Studies in Thermal Engineering)
Augmented heat transfer efficacy with structural strengthening for an internally cooled gas turbine blade fosters innovative types of latticework composed by crossed zig-zag ribs, wavy ribs, offset circular or diamond-shaped pin-fins, which are arranged on opposite endwalls of a rectangular channel with lateral flow. Research novelty focuses on their attributing flow structures that constitute prolific mechanisms of heat transfer enhancement. Prior to delving into the analysis of Nusselt numbers, friction factors and aerothermal performance factors, the streaklines are correlatively showcased with fluid velocity, turbulent kinetic energy, and temperature fields. Following a favorable experimental verification, the analogical flow and heat transfer analysis from the perspectives of vortex cores and synergy angles, as well as the correlations devised from simulated Nusselt numbers and friction factors, complement the aerothermal advancements across present latticework morphologies with significant Nusselt number elevations to 4.5–8.42 times Dittus-Boelter references and aerothermal performance factors of 0.68–1.09 at Reynolds numbers of 10,000–30,000, thereby contributing to academic knowledge and practical applications.